2014
DOI: 10.1021/jf4055374
|View full text |Cite
|
Sign up to set email alerts
|

Fumagillin: An Overview of Recent Scientific Advances and Their Significance for Apiculture

Abstract: Fumagillin is a potent fungal metabolite first isolated from Aspergillus fumigatus. It is widely used in apiculture and human medicine against a variety of microsporidian fungal infections. It has been the subject of research in cancer treatments by employing its angiogenesis inhibitory properties. The toxicity of fumagillin has limited its use for human applications and spurred the development of analogues using structure-activity relationships relating to its angiogenesis properties. These discoveries may ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 117 publications
2
55
0
3
Order By: Relevance
“…Using Fumagilin-B ® or Fumidil-B ® therefore introduces not only one, but two potentially biologically active compounds to the bee hive (van den Heever et al 2014). We observed that the risk of bee mortality of N. ceranae -infected caged bees treated with DCH alone was not statistically different compared to the commercial Fumagilin-B ® for most of the study period, with the exception of days 11 and 17 (Table II).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Using Fumagilin-B ® or Fumidil-B ® therefore introduces not only one, but two potentially biologically active compounds to the bee hive (van den Heever et al 2014). We observed that the risk of bee mortality of N. ceranae -infected caged bees treated with DCH alone was not statistically different compared to the commercial Fumagilin-B ® for most of the study period, with the exception of days 11 and 17 (Table II).…”
Section: Discussionmentioning
confidence: 88%
“…The environmental prevalence of DCH also needs to be established in order to ascertain if this route of contamination is indeed of concern not only for beekeeping, but also for human health (van den Heever et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations